2022
DOI: 10.1186/s40104-022-00737-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG ameliorates DON-induced intestinal damage depending on the enrichment of beneficial bacteria in weaned piglets

Abstract: Background Deoxynivalenol (DON) is one of the most common environmental pollutants that induces intestinal inflammation and microbiota dysbiosis. Lactobacillus rhamnosus GG (LGG) is a probiotic that not only has anti-inflammatory effects, but also shows protective effect on the intestinal barrier. However, it is still unknown whether LGG exerts beneficial effects against DON-induced intestinal damage in piglets. In this work, a total of 36 weaned piglets were randomized to one of four treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Previous study found increased Odoribacter in fecal microbiota transplantation-treated colitis mice ( Zhang et al, 2020 ), which was in line with LPS-induced mice, and higher concentration treatment of BLBP depicted a higher abundance of Odoribacter in mice in group GE ( p < 0.01). Lactobacillus is a commonly recognized genus of probiotics, which can maintain the intestinal barrier and provide protection against inflammation ( Bai et al, 2022 ), and a lower abundance of Lactobacillus had been found in antibiotic-associated diarrhea in mice ( Chen C. et al, 2022 ) and ulcerative colitis mice ( Hu et al, 2022 ). In the current study, a higher abundance of Lactobacillus was detected in mice in all BLBP-supplemented groups, especially in group GC and GE, which was in accordance with Lycium barbarum arabinogalactan treated mice with colitis ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found increased Odoribacter in fecal microbiota transplantation-treated colitis mice ( Zhang et al, 2020 ), which was in line with LPS-induced mice, and higher concentration treatment of BLBP depicted a higher abundance of Odoribacter in mice in group GE ( p < 0.01). Lactobacillus is a commonly recognized genus of probiotics, which can maintain the intestinal barrier and provide protection against inflammation ( Bai et al, 2022 ), and a lower abundance of Lactobacillus had been found in antibiotic-associated diarrhea in mice ( Chen C. et al, 2022 ) and ulcerative colitis mice ( Hu et al, 2022 ). In the current study, a higher abundance of Lactobacillus was detected in mice in all BLBP-supplemented groups, especially in group GC and GE, which was in accordance with Lycium barbarum arabinogalactan treated mice with colitis ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors can bind to the membrane receptor TLR4, then trigger the TLR4/NF-κB signaling pathway to secrete a large number of inflammatory cytokines, and eventually lead to tissue damage ( 46 ). LGG ameliorated DON- and LPS-induced inflammation by modulating the TLR4/NF-κB signaling pathway ( 47 , 48 ). A recent report showed a new soluble protein from LGG, HM0539, suppress inflammation by inhibiting the TLR4/MyD88/NF-κB signaling, which is considered as a potential therapeutic option for inflammatory bowel disease (IBD) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 The TLR4/NF-κB signaling pathway was activated in DON-induced intestinal toxicity and hepatotoxicity, and LGG can inhibit the TLR4/ NF-κB signaling pathway to alleviate intestinal inflammation and liver damage. 81,82 4.4. Notch 1.…”
Section: Foxomentioning
confidence: 99%